IMPLEMENTASI KURIKULUM IMAN DAN AL-QUR'AN DI KUTTAB IMAM AL GHAZALI SUKABUMI - Nisa Putri Wulandari; Siti Qomariyah, Venti Fatmawati Suhendra, Salma Tsana Fi Sa'adah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The Islamic Religious Education curriculum is still not fully successful in forming students who have strong faith and devotion to Allah Ta'ala. The shortcomings in the position of the Islamic Religious Education curriculum in forming a complete Islamic personality in students are a factor that is noticed, whether realized or not. The Kuttab Imam Al Ghazali Sukabumi has a mission to restore the glory of science by implementing the faith and Qur'an curriculum. This study aims to describe how the faith and Qur'an curriculum at Kuttab Imam Al Ghazali Sukabumi is implemented to form faith characters. In this research, a qualitative case study method was used. Data analysis was conducted using the Miles and Huberman model. From the results of the study, it was found that the curriculum used in Kuttab Imam Al Ghazali Sukabumi is the Qur'anic curriculum and the faith curriculum, which is also known as the first-century hijri curriculum or the prophet curriculum. In general, this curriculum emphasizes the concept and stages of faith before Qur'an and adab before knowledge, with Qur'an, sunnah. No significant obstacles were found in the implementation of this curriculum, in fact it can be said that the obstacles were very minimal.